Investigating the ease-of-retrieval effect in an eyewitness context. Issue 2 (7th February 2021) - Groncki, Roy; Beaudry, Jennifer L.; Sauer, James D.
ABSTRACT: The way in which individuals think about their own cognitive processes plays an important role in various domains. When eyewitnesses assess their confidence in identification decisions, they could be influenced by how easily relevant information comes to mind. This ease-of-retrieval effect has a robust influence on people's cognitions in a variety of contexts (e.g., attitudes), but it has not yet been applied to eyewitness decisions. In three studies, we explored whether the ease with which eyewitnesses recall certain memorial information influenced their identification confidence assessments and related testimony-relevant judgements (e.g., perceived quality of view). We manipulated the number of reasons participants gave to justify their identification (Study 1; N = 343), and also the number of instances they provided of a weak or strong memory (Studies 2a & 2b; N s = 350 & 312, respectively). Across the three studies, ease-of-retrieval did not affect eyewitnesses' confidence or other testimony-relevant judgements. We then tried – and failed – to replicate Schwarz, N., Bless, H., Strack, F., Klumpp, G., Rittenauer-Schatka, H., & Simons, A. (1991. Ease of retrieval as information: Another look at the availability heuristic. Journal of Personality and Social Psychology, 61 (2), 195–202. doi:10.1037/0022-3514.61.2.195) original ease-of-retrieval finding (Study 3; N = 661). In three of the four studies, ease-of-retrieval had the expected effect on participants' perceived task difficulty; however, frequentist and Bayesian testing showed no evidence for an effect on confidence or assertiveness ratings.